ANTECEDENT EXPERIENTAL MARKETING, IKATAN EMOSIONAL, KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA TOKO ZAMZAM DI SALATIGA - Aini, Lutfia Nurul (Master of Management Diponegoro University, 2011)
Retail business is a distribution chain link which is influencing individuals' life both directly and indirectly. However, the rapid development of modern market often raises a complaint from some parties such as traditional market even from co-retail. Costumers are unwilling to visit Toko Zam-Zam because of the less maximal services and the lazy waiters. But, there is no costumers engaging program. Thus, costumers are having no difficulties to move to other markets.This research analyses the improvement of costumers' loyalty through experiential marketing and emotional bonds at Tako Zam-Zam Salatiga. The research problem based on 2 (two) matters, research gap based on previous research, for example research limitation and direction for future research and inconsistent of previous findings such as in Yu-Jia Hu (2009); Wijaya & Thia (2007) dan Christina (2006); Amir Hamzah (2007); Fransisca Andreani (2007); Schmitt (1999); Rachmawati (2009); Chang & Tu (2005); Yu-Jia Hu (2009). The second one is based on research problem found in data of Toko Zam-Zam Salatiga overall performance and sales objective.This research is conducted to find out factors that influence marketing experiential and emotional bonds which increase future costumers' loyalty. On this research, a theoretical model with eight hypotheses, which is tested by Structural Equation Model (SEM), is developed. The respondent is taken from the costumers of Toko Zam-Zam. The total respondents are 153.The result of SEM data processing for complete model with modification index fulfills the goodness of fit criteria. Therefore, it can be concluded that the model is fit tr: be used. The research result shows that Costumer Satisfaction may be improved by increasing experiential marketing and emotional bonds in Toko Zam-Zam Salatiga. Then, higher Service Satisfaction will increase Costumers Loyalty of Toko Zam-Zam Salatiga.